Quinones operate as proton-collecting antennas in energy-transducing membranes - Adel Beghiah; Niusha Bagheri; Sofia Badolato; Hyunho Kim; Timir Baran Sil; Maximilian C. Pöverlein; Jerker Widengren; Ville R. I. Kaila (Proceedings of the National Academy of Sciences, 2026)
The bioenergetic complexes of energy-transducing membranes generate a proton current that powers the synthesis of adenosine triphosphate. Yet, since the early days of the chemiosmotic theory, it has remained elusive and much debated whether the proton motive force (PMF) delocalizes into the bulk solvent surrounding the energy-transducing membrane or if the thermodynamic force is exerted as a localized proton current along the membrane surface. To elucidate the molecular principles underlying protonation dynamics at biological membranes, we combine here proteoliposome experiments with fluorescence correlation spectroscopy and multiscale molecular simulations. We show that ubiquinone (Q 10 ), which is an essential electron carrier of inner mitochondrial membranes, interacts with protons at the membrane, and alters the rate of the protonation reactions along the surface. We find that physiological Q 10 concentrations increase the integrity of the liposome membranes to sustain a PMF and enhance the rate of surface protonation reactions of lipid-conjugated pH-sensitive fluorophores, occurring on a microsecond timescale. Our multiscale simulations reveal that the quinone headgroup localizes at the membrane surface and stabilizes protonated water species by cation–π and hydrogen-bonded interactions amplifying the proton exchange on the surface relative to the bulk solvent. We suggest that in addition to the well-established role of quinones as redox mediators in energy-transducing membranes, Q 10 also promotes the proton-collecting antenna effect, mediating proton exchange along the membrane and supporting a local proton circuit model. Our combined findings provide molecular insight into propagation of proton currents along biological membranes and reveal key principles underlying the energy conversion mechanisms in biology.